Sanur Special Economic Zone as Milestone of Future Quality Tourism in Bali - Ida Bagus Gede Karyambara Putra (Bali Tourism Journal, 2022)
Despite the growing global tourism industry that proposes unforgettable leisure experiences, Bali continuously holds the top of mind as one of the best world-class tourism destinations. However, the Indonesian government planned to transition from mass tourism to quality tourism. The government and tourism businesses were required to improve the quality of tourism to survive in the industry’s competition. Proposed in a concept of potential regional development and a sustainable economy, the central government, in collaboration with Bali provincial government, launched the 19th Special Economic Zone. The special economic zone, or Kawasan Ekonomi Khusus (KEK), was built in Sanur with IDR 10.2 trillion worth of investment commitment from PT Pertamina Bina Medika (IHC). The area encompasses 41.26 hectares, complemented by the brand-new look of the Grand Inna Bali Beach (GIBB) Hotel, supported with various facilities such as the Convention Center, Ethnomedicinal Botanic Gardens, and Commercial arcades to accommodate local MSMEs. The presence of health tourism complements the diversity of wellness tourism inherent on the island of God. This Sanur Special Economic Zone is the future hope of well-organized and sustainable tourism. The investment was said to be a bold move to mature and refresh Bali’s cultural tourism.